Evaluation of Cow Bone and Snail Shell for Surface Treament of Low Carbon Steel - Oinu, Oinu Timothy; Gundu, D.T. Gundu; Nyior, G. B. Nyior (Natural Science Journal, 2022)
Purpose: In this study, selected calcareous wastes (cow bone and snail shell) were evaluated for use in surface carburizing of low carbon steel. Methodology: Pack carburization process was used for the surface hardening of mild steel at 800 oC as the carburizing temperature. The soaking period of 2 hours was used and water was used as quenching medium. The specimens were subsequently tempered at 500. Mechanical tests such as hardness, impact, microstructural and wear resistance were carried out on the samples using standardized methods. Results: The results obtained showed that the sample carburized with snail shell gave a higher hardness value than sample carburized with cow bone and untreated sample. In the charpy impact test carried out, it was observed that the sample carburized by snail shell has higher energy value than sample carburized with cow bone. For microstructural analysis test, it was seen that sample carburized by cow bone gave equiaxed and finer grains than sample carburized with snail shell and untreated sample, and for wear rate test, sample carburized by snail shell, has a better wear rate than sample carburized by cow bone and untreated sample.